(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article clarifies a single, practical purpose for California’s climate era: to convert ambitious targets into reliable, equitable delivery—clean electricity and the grid to carry it, low-carbon mobility and housing options, safe water and coasts, and climate-ready neighborhoods—on timelines that match the science. The argument is constructive and human: California already has the core authorities; the work now is to align them around one North Star—build clean, build fair, build fast—so plans become projects and projects become outcomes at scale. The paper synthesizes how statutory targets (AB 32, SB 32, SB 100), planning instruments (Scoping Plans), and cornerstone laws (CEQA, SGMA) can be coordinated with programmatic review, time-certain processes, and public metrics to achieve dependable implementation without adding new mandates